Peran Kepuasan Kerja Dalam Meningkatkan Disiplin Guru SMAN Di Kabupaten Buru Selatan Kecamatan Namroleh - Momin Tomanussa; Rugaiyah -; Eliana Sari (Jurnal Ilmiah Wahana Pendidikan, 2018)
This study aims to examine the role of job satisfaction in improving teacher discipline in Namrole District, South Buru District, Maluku Province. This research will be conducted in four SMANs of Namrole Sub-district of South Buru Regency of Maluku Province. Research in maret until june 2018. The research approach used is qualitative approach. Qualitative is one method of research in social sciences. The results show that the discipline of Teacher Work 1) Increase the discipline of teaching. 2) Improving Disciplinary Planning, 3) Improving Discipline Implementation of Learning. 4) Improving Discipline Evaluation of Learning 5) Internal and External Factors Affecting Master's Job Satisfaction. 6) Supporting Factors and Inhibitors Teacher Job Satisfaction